Effectiveness of teaching strategies for moral education - Cui, Guo; Yasin, Maizura; Saharuddin, Norzihani (Human Resource Management Academic Research Society, 2024)
The strategic research of moral education plays an important role in the field of education. Exploring the effectiveness of moral education is a major topic for improving and promoting educational strategies. This study examines the effectiveness of moral education through focus groups. This study used purposive sampling to conduct focus group interviews with 14 participants in a public university located in Selangor, Malaysia, which were recorded using an electronic audio recording device and transcribed verbatim upon completion, and the textual content was analysed and categorised using thematic coding. Finally, the data are analyzed and interpreted through the theoretical framework of constructionism. Through the results of this study, it is found that the strategy of enhancing life reality and experiential learning, and using teachers as facilitators to conduct moral education is more effective, it is effective for students to participate in moral education in life while seeking strategic education courses. This study may provide a theoretical basis for learning theory and moral development theory, and help policy designers in curriculum design. In general, based on the teaching effectiveness discussed in this study, it will help the innovation of curriculum and teaching methods, and in the future, we encourage more research to adopt the constructivist perspective for analysis.